Compliance Level to Food Labelling Regulation for Micro and Small-sized Enterprises Products: A Descriptive Study in Wonosobo District, Indonesia - Rimbawan Rimbawan; Anna Vipta Resti Mauludyani; Akifa Laila Rusyda (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2023)
Food labelling is an effective tool in protecting consumer health with respect to safety and nutrition. Complying with labelling regulations is essential in preventing product recalls. Thus, the objective of this study was to determine the extent of adherence to food labelling regulations by micro and small-sized enterprises (MSEs) in Wonosobo District, in accordance to the existing guidelines. Primary data were collected through a market survey approach, with analysis conducted through purposive sampling in shops, stalls, home industries, markets, and supermarkets. Content analysis was employed to evaluate four categories of processed food: flour/starch-based products, water-based flavored drinks, processed fruit products, and processed grain, nut, and tuber products, totaling 92 products. The compliance level with labelling regulations was evaluated based on the principal display panel, labelling formats, general labelling requirements, and prohibited statements on the label. The results revealed that the compliance level of labelling flour/starch-based products was good, with an average of 75%. In contrast, the average compliance level for water-based flavored drink products was 58%, while the average compliance levels for processed fruit products and processed grain, nut, and tuber products were 54 and 59%, respectively, indicating a lower level of compliance compared to flour/starch-based products.